Going, going, gone! - Kettle,Phil; Webb , Melissa (Australia, South Yarra, Vic.: Macmillan Education Australia, 2011)
The Get Real! series written by Phil Kettle are hilarious short novels that will keep all 7-10 year olds hooked. They will especially appeal to reluctant readers. Fabulous ideas for reading and writing feature at the back of each book including Let's Write, About the Author and Illustrator, and A Laugh a Minute! In Going, Going, Gone, it's just another extraordinarily average, boring and uneventful day at Average Primary School. But Jesse and Harry aren't too worried. Why? Because today is the second last day of the school year, which means tomorrow is the last day of the school year. And the boys have planned a huge day of celebrations - Jesse and Harry style. Let the fun begin - again!
Keywords: English, Fiction